Contrast-Enhanced Ultrasound of Fibrolamellar Hepatocellular Carcinoma Kontrastmittelsonografie eines fibrolamellären hepatozellulären Karzinoms - Wildner, Dane; Schlitt, Hans Jürgen; Bäuerle, Tobias; Haibach, Martina (TumorDiagnostik & Therapie, 2022)
We present the case of a 24-year-old male patient, who was admitted for endoscopy due to sustained pain in the upper abdomen with nausea and postprandial fullness without vomiting for more than 5 months. In the physical examination, an epigastric induration was found. Endoscopy revealed an external impression of the proximal duodenum. Beyond that, normal findings could be ascertained in gastroscopy and ileo-colonoscopy. Abdominal ultrasound identified a large hypoechoic lesion in the left liver lobe with a sharp delineation. Along the upper mesenteric vessels, enlarged lymphnodes were visible with contact to the proximal duodenum. Contrast-enhanced ultrasound (CE-US) was conducted and revealed the typical perfusion pattern of hepatocellular carcinoma. For further assessment, an ultrasound-guided core-biopsy of the lesion was performed. The histopathological evaluations resulted in the diagnosis of a hepatocellular carcinoma of fibrolamellar subtype. With the present case, we want to illustrate the perfusion pattern of a fibrolamellar hepatocellular carcinoma in contrast-enhanced ultrasound. Even though the tumor tissue is surrounded by lamellar bands of fibrosis with collagen-rich fibers, the perfusion pattern is consistent with the previously known appearance of HCC in CE-US.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Contrast-Enhanced Ultrasound; Fibrolamellar Hepatocellular Carcinoma; Liver